Efforts To Improve Learning Achievement Of Class VII A SMP Negeri 1 Latambaga In Learning History Of Islamic Culture Through Information Search Method Study Year 2018/2019 - Mutmainnah (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
This study aims to describe student achievement in learning Islamic Cultural History in class VII A SMP Negeri 1 Latambaga after using the Information search method. The research model used in this research is Classroom Action Research. The object in the study was 30 students of class VII A SMP Negeri 1 Latambaga. The instruments in this study were observation or observation sheets and Indonesian language learning tests. Data analysis was carried out by using qualitative descriptive techniques. The results obtained by referring to the minimum completeness criteria (KKM) are 70%. In the pre-cycle, the classical completeness was obtained by 13 students or 43.33% who reached the learning completeness indicator with a value of ≥ 65, while those who did not achieve completeness were 17 students or 56.67%. The results of the first cycle obtained classical completeness were 24 students or 80% who reached the learning completeness indicator with a value of ≥ 65, while those who did not achieve completeness were 6 students or 20%. The results of the second cycle obtained classical completeness were 28 students or 93.33% who reached the learning completeness indicator with a value of ≥ 65, while those who did not achieve completeness were 2 students or 6.67%. Student achievement in learning Islamic Cultural History in class VII A SMP Negeri 1 Latambaga after using the Information search method has increased from the implementation of the pre-cycle / pre-action to the implementation of the final evaluation of cycle II.